Back Cover: Structural and Spectroscopic Comparison of Soft‐Se vs. Hard‐O Donor Bonding in Trivalent Americium/Neodymium Molecules (Angew. Chem. Int. Ed. 17/2021). Issue 17 (22nd March 2021) - Goodwin, Conrad A. P.; Schlimgen, Anthony W.; Albrecht‐Schönzart, Thomas E.; Batista, Enrique R.; Gaunt, Andrew J.; Janicke, Michael T.; Kozimor, Stosh A.; Scott, Brian L.; Stevens, Lauren M.; White, Frankie D.; Yang, Ping
Abstract : Differential covalency in trivalent actinide versus lanthanide bonding with soft donors can aid separations. In their Research Article on page 9459, Enrique R. Batista, Andrew J. Gaunt, Ping Yang, and co‐workers compare electronic structure and bonding with isoradial Am 3+ and Nd 3+ using hard O‐ and soft Se‐donor ligands. The first structural characterization of molecular Am–Se bonding, along with spectroscopy and ab initio calculations, is used to evaluate f‐orbital involvement for Am 3+ versus Nd 3+ and explain structural trends. Graphic designed by Josh Smith, Chemistry Division, Los Alamos National Laboratory.